2021
DOI: 10.5770/cgj.24.506
|View full text |Cite
|
Sign up to set email alerts
|

Online Educational Tools for Caregivers of People with Dementia: A Scoping Literature Review

Abstract: Background  Informal caregivers of people with dementia provide the majority of health-based care to people with dementia. Providing this care requires knowledge and access to resources, which caregivers often do not receive. We set out to evaluate the effect of online educational tools on informal caregiver self-efficacy, quality of life, burden/stress, depression, and anxiety, and to identify effective processes for online educational tool development.  Methods  We conducted a scoping review of articles on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
(323 reference statements)
2
9
0
1
Order By: Relevance
“…First, the beneficial effects of the Tele-Health intervention program on home-dwelling persons with dementia or MCI and their primary caregivers were confirmed due to a significant reduction in the participant’s NPI intensity and their primary caregiver’s stress level. These findings are consistent with results gained from previous studies on the effect of Tele-Health-based intervention on persons with dementia and caregivers [ 29 , 30 , 31 , 32 , 33 ]. Since the Tele-Health intervention program (digitally delivering supportive care services to households) protects against the infection of COVID-19, the development of more sophisticated Tele-Health intervention programs could be essential—given the potential risk of future pandemics—for the Taiwanese government to assure continuous care provisions for those who are in need of dementia care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, the beneficial effects of the Tele-Health intervention program on home-dwelling persons with dementia or MCI and their primary caregivers were confirmed due to a significant reduction in the participant’s NPI intensity and their primary caregiver’s stress level. These findings are consistent with results gained from previous studies on the effect of Tele-Health-based intervention on persons with dementia and caregivers [ 29 , 30 , 31 , 32 , 33 ]. Since the Tele-Health intervention program (digitally delivering supportive care services to households) protects against the infection of COVID-19, the development of more sophisticated Tele-Health intervention programs could be essential—given the potential risk of future pandemics—for the Taiwanese government to assure continuous care provisions for those who are in need of dementia care.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies found little or no effect of the Tele-health intervention program on caregivers’ burdens, depressive symptoms, and health-related quality of life [ 27 ], and found insignificant improvements in objective caring skills [ 28 ]. Conversely, other research revealed that the Tele-Health intervention program not only improves quality of life and ameliorates neuropsychiatric symptoms in persons with dementia or MCI, but also leads to a better health outcome for primary caregivers of persons with dementia or MCI, a lower risk of mental health impairment [ 29 , 30 , 31 , 32 ], burden reduction [ 29 , 33 ], and improvements in knowledge of dementia [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of both types have hitherto been examined in narrative, 127 scoping 129,131 and systematic reviews. 25,128,130 Results range from improvements in subjective 127 or objective only 130 to both. 25,128,131 Yet these reviews also exhibit the between-intervention heterogeneity that our review has highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…En el ámbito de la salud mental, las terapias basadas en internet, ehealth, han mostrado resultados prometedores, y las publicaciones sobre el tema son numerosas (18,19) , sin embargo, los profesionales de enfermería se han aproximado a las TICs como terapia de forma poco relevante. Aunque en algunos estudios se constatan iniciativas enfermeras en este ámbito (20)(21)(22) , ninguna de las publicaciones localizadas tenía un diseño experimental ni se centró en el manejo de la ansiedad desde la psicoeducación.…”
Section: Chow Et Al (12)unclassified